FATOR DE FORMA NOS MATERIAIS ANTIVIBRÁTICOS - Susana Beatriz Gandra Dias (2021)
Buildings and their construction are responsible for a large portion of the energy consumed worldwide and also for CO2 emissions into the atmosphere. In addition to environmental concerns, more and more attention has been paid to the comfort of those who live, work or frequent a building, resulting in a greater focus on thermal, acoustic and vibration insulation. The lightweight construction has emerged as a solution for this industry that allows greater versatility in construction and in the materials to be used. This work presents a study on cork and rubber composites used for vibration control in flooring. In conjunction with Amorim Cork Composites (ACC), the study's main objectives were to lower the load ranges in which composites are used, in order to meet market needs, as well as to reduce their natural frequency and dynamic stiffness by changing their shape factor. Thus, static and dynamic simulations were performed, using ANSYS Mechanical software, to understand the effect of the shape factor on the composites behaviour and to choose the geometries to be reproduced and experimentally tested. It was found that, both in the static and dynamic domain, in general, the decrease of the shape factor leads to the decrease of the dynamic stiffness and natural frequency - starting from a reference sample and introducing grooves and perforations to reduce the shape factor. The main objectives were achieved since a reduction of the lower limit of the load range was obtained and, at the same time, there was approximation of the limits of the load range. It was also possible to decrease the natural frequency and dynamic stiffness of the material under study, which improves its ability to control vibrations. The best results were obtained for the sample with the lowest form factor. There were maximum reductions in dynamic stiffness and natural frequency by 39 and 25%, respectively.